Application Of Balanced Scorecard As A Benchmark For Performance Assessment In Service Companies: Case Study At PT. Mitra Intertrans Forwarding Surabaya Branch - Diana Zuhro (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the internal and external environment of PT MIF Surabaya, namely to find out what factors are the strengths and weaknesses of the company as well as knowing the opportunities and threats faced by the company and formulating the best and most suitable marketing strategy for PT MIF Surabaya by taking into account internal factors (strengths and weaknesses) and external factors (threats and opportunities) to face business competition in the field of Domestic Forwarding and Logistics. One of PT Meratus Line's strategies in developing market penetration in Indonesia is through the formation of PT MIF which was determined by the Decree of the Minister of Justice of the Republic of Indonesia No.C2.734.HT.01.01 – 1991 dated March 6 1991, and published in Supplement to the State Gazette of the Republic of Indonesia No. 26 dated March 3 1992. During this period, it caused quite a lot of concern for other Forwarding Companies which had become Meratus Line customers. With commitment and proof from the Meratus Group that MIF is not permitted to compete for customers from Forwarding Companies that use Meratus Line services, PT MIF has succeeded in becoming